Kesalehan Performatif dan Deviasi Tersembunyi: Dinamika Sosio-Religius Praktik Mokel pada Bulan Ramadan di Indonesia - Moh. Nadhif; Junaidi Mistar; Djunaidi Ghony; Bakri Muhammad Bakhiet (AL-BAYAN INSTITUTE, 2026)
The practice of mokel eating or drinking secretly during the fasting hours of Ramadan represents a unique socio-religious phenomenon within Indonesian Muslim communities, yet it has rarely been examined in academic literature beyond moral or normative perspectives. Most existing studies frame the practice merely as a violation of religious obligations, overlooking the complex social dynamics that shape religious behavior in communal contexts. This study aims to analyze mokel practices through the lens of performative piety and hidden deviance to better understand the tension between publicly displayed religiosity and privately concealed religious transgression during Ramadan. The research addresses the following questions: (1) how do individuals who engage in mokel negotiate their religious identity within a community that strongly upholds the norms of Ramadan fasting? and (2) what socio-religious factors contribute to the emergence and persistence of mokel practices in Muslim society? This study employs a qualitative research design using a socio-religious approach. Data were collected through in-depth interviews, participant observation, and documentation within selected Muslim communities where mokel practices are socially recognized. The collected data were analyzed using thematic analysis to identify patterns of religious behavior, social expectations, and individual rationalization. The findings reveal that mokel practices are not simply acts of individual religious deviance but reflect a complex negotiation between social pressure to demonstrate public piety and personal limitations in fulfilling religious obligations. Individuals who engage in mokel often maintain outward participation in religious rituals to preserve social belonging while privately managing their religious shortcomings. This dynamic illustrates the coexistence of performative piety and hidden deviance within communal religious life, highlighting the gap between normative religious ideals and lived religious practices. The study contributes to broader discussions in the sociology of religion by offering a new perspective on hidden religious behavior in Muslim societies during Ramadan